Pengembangan LKPD Konsep Perbandingan Etnomatematika pada Makanan Khas Bengkulu, Lemang - Mutiara, Dea; Ristontowi, Ristontowi; Etmy, Desventri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to develop a Student Worksheet (LKPD) on the concept of ethnomathematic comparison of Bengkulu's traditional food, namely lemang. This study uses the Research and Development (R&D) method with a 4D development model that includes the Define, Design, and Develop stages. The research subjects consisted of 28 seventh-grade students at SMP Negeri 10 Bengkulu City. The instruments used were expert validation sheets and teacher and student response questionnaires to measure the level of validity and practicality of the product. The results showed that the developed LKPD obtained a validity level of 92.7% with a very valid category. In addition, the results of the practicality test showed an average value of 85.3% with a very practical category. This indicates that the LKPD based on ethnomathematics in the context of lemang is suitable for use in mathematics learning, especially on comparison material. Conclusion, The use of local cultural contexts has also been proven to be able to increase students' interest and understanding of mathematical concepts in a more contextual and meaningful way. Keywords: LKPD; ethnomathematics; comparison; lemang; development.